Hubungan Antara Lama Duduk Tanpa Sandaran Dengan Resiko Terjadinya Low Back Pain Pada Pekerja Mebel Di Pt. Marleny Jepara - Nisa, Fitria Fahrun, Maskun Pudjianto, M.Kes (2017)
Low Back Pain or LBP is a pain syndrome that occurs in the lower back region and is an occupational musculoskeletal disorders are excessive, the most common cause stretching of a muscle or a wrong posture. Another thing that can cause them LBP stool habits, work with a bent position with a long time, lifting and carrying the load in a manner that is not ergonomic, and degeneratife disease. Knowing their long relationship stool against the risk of low back pain in workers furniture PT. Marleny Jepara. Provide information and knowledge on health, especially on ergonomics when doing the job. Peneletian types namely cros ssectional study by using a simple method of sampling purposive sampling to obtain the number of respondents as many as 35 people. Measuring instrument using REBA scale questionnaire and ODI. Data analysis technique using chi-square. The results of the test values obtained value with the value 0.017 p≤ 0.05 which means that Ho refused and Ha is received it can be concluded their long-standing relationship stool against the occurrence of low back pain in workers furniture PT. Marleny Jepara. Keywords: Sitting without a backrest, Low Back Pain (LBP).